(untitled) (The Agriculturists, 2014)
An experiment was conducted at Microbiology Laboratory of Plant Pathology Department, Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU) during 2007 to determine the virulence and variation in symptom development by Fusarium oxysporum f. sp. phaseoli isolates at different growth stages such as emergence and early vegetative stage, branching and rapid vegetative growth stage and early flowering stage of Bush bean, and in-vitro control of the pathogen with the selected fungicides. Eight isolates of this pathogen were collected from different pathology laboratory of BARI, BAU and BSMRAU. IS3 isolate collected from Bushbean seeds were found most virulent in pathogenicity test such as pre-emergence mortality, root rot, root lesion, leaf yellowing and wilting when this isolate was inoculated at different growth stages of bush bean. Four fungicides such as Vitavax, Rovral, Cupravit and Aimcozim were evaluated invitro to test the efficacy against isolate IS3. Aimcozim at different concentration (50-400 ppm) was found most effective in in-vitro evaluation. DOI: http://dx.doi.org/10.3329/agric.v12i1.19865 The Agriculturists 2014; 12(1) 103-110